Kepuasan Kinerja Guru Matematika Ditinjau dari Pengaruh Supervisi Kepala Sekolah dan Motivasi Kerja Guru - Virgana Virgana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2014)
This research is aimed at obtaining information related to the possibility that the Mathematics teachers’job satisfaction is caused by supervision of principal and motivation of teacher. Research has been implemented using correlation after all variables put into a matrix of correlation. In this research, teachers had been chosen as a unit analysis and 60 samples selected randomly. The result of analysis finds out that: 1) the Matematics teachers’ job satisfaction is caused by supervision of the principal 2) the teachers’ job satisfaction is caused by motivation and 3) the teachers’ job satisfaction is caused by supervision of the principal and motivation of the teachers together. Therefore, supervision of the principal and motivation of the teachers should be put into account of human resources development in managing in teaching activities in the classroom. However other variables are necessary to be taken into account properly.